Introducing a new trio effects portable water treatment plant for rural areas - Oluwasoga, Akindoyo Edward (2013)

(untitled)
Water is Life, the quantity, usage, consumption and the importance of water in our daily activities, domestic purposes and industrial cannot be overemphasized, thus water remains an important aspect of the Human existence as we cannot do without water. The treatment and removal of MTBE (Methyl Tert-Butyl Ether) in water especially from petrochemical waste water is of immense importance and had been a challenging one because most of the available techniques in its removal can only remove part and not the whole, it is on this note that the treatment measure here shall be adopting a Trio effect to remove this contaminant from a sample of contaminated water. Treatment of Methyl Tert-Butyl Ether (MTBE) from wastewater supplies presents specific challenges due to the physicochemical properties of MTBE which depend strongly on its hydrophilic nature, and translate into a high solubility in water. MTBE has very low Henry’s constant and very low affinity for common adsorbents. An investigation was carried out for the treatability of methyl tert-butyl ether (MTBE) in synthetic wastewater. In this research, experimental rig and bench-scale studies using granular activated carbon (GAC) and hydrogen peroxide (H2O2) were conducted to observe the treatability of MTBE in synthetic wastewater. An experimental rig was built up that consist of three conjugated system. Subsequently, MTBE was amended to the H2O2 and air flow, followed by adsorption treatment with GAC. Generally, the major finding suggests that the longer cycle pulsation time (3 minutes open valve + 5 seconds closed valve) with air flow rate at 6 L/min over the synthetic wastewater caused a greater removal of MTBE. The result of this study can help to provide specific guidance into process parameter selection for treating MTBE in wastewaters. The optimum operating conditions are very important for treating the wastewater effectively in a larger scale. Moreover, this project shall be looking also into the commercialization of this plant to the market, thus markets surveys, researches and other techniques are also be carried out to introduce the plant to the market.